Carotid atherosclerotic plaque stenosis: the stabilizing role of statins. (4th October 2014) - Artom, Nathan; Montecucco, Fabrizio; Dallegri, Franco; Pende, Aldo
Abstract Background Both pathophysiology and treatments of carotid atherosclerotic plaque stenosis represent two interesting fields of strong scientific investigation. Among different drugs, safety and efficacy of statin treatment have been widely investigated and proved. Materials and methods This narrative review is based on the material searched for and obtained via MEDLINE and PubMed up to March 2014. The search terms we used were: 'carotid plaque, intima‐media thickness, plaque burden, stroke' in combination with 'statins, pleiotropic effects, HMG‐CoA reductase inhibitors, lipid‐lowering drugs'. Results Carotid stenosis represents both a useful parameter to evaluate the atherosclerotic burden and a target for therapeutic (medical or surgical) decisions. Statins do not only improve the lipid profile, but also induce some 'pleiotropic' anti‐inflammatory activities that contribute to carotid plaque stabilization. Statin‐mediated protective activities are under active investigation at subclinical levels with the potential benefit of advanced imaging techniques. However, considering that some new techniques (excepted B‐mode ultrasound) remain quite expensive, they can have for the moment an important role in research, but not in the clinical field. Conclusions Emerging evidence suggests that statin treatment improves carotid atherosclerosis, inducing a partial regression of plaque inflammation and size. Innovative imaging techniques might also ameliorate the identification of patients at high risk of cerebrovascular and coronary events, for which preventive statin treatments might be essential.